Recommendations in social inquiry reports, 1976-1977; follow-up - Hardiker, Pauline (UK Data Service, 1980)
The purpose of this study was to identify probation officers' ideologies of crime and to describe the aims and factors which are associated with the different recommendations probation officers make in their social inquiry reports.